2005
DOI: 10.1200/jco.2005.01.4886
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Malignant Peripheral Nerve Sheath Tumor: The Italian and German Soft Tissue Sarcoma Cooperative Group

Abstract: MPNST is an aggressive tumor for which complete surgical resection is the mainstay of successful treatment. Postoperative radiotherapy may have a role in improving local control in patients with minimal residual tumor. The reported responses to primary chemotherapy suggest that it may be effective in patients with tumor considered unresectable at diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

24
352
4
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 312 publications
(381 citation statements)
references
References 19 publications
24
352
4
1
Order By: Relevance
“…The present subset of extremity cases confirms our main findings in NRSTS of all sites, reported elsewhere [9][10][11], i.e., quite a satisfactory overall outcome (5-year OS 84%), the prognostic role of IRS grouping, grade of malignancy, tumor size and local invasiveness, the poor prognosis for patients with the MPNST histotype [12] and with metastases at diagnosis. It is worth noting that treatment for extremity NRSTS proved more effective over the years, while this was not the case for RMS.…”
Section: Discussionsupporting
confidence: 91%
“…The present subset of extremity cases confirms our main findings in NRSTS of all sites, reported elsewhere [9][10][11], i.e., quite a satisfactory overall outcome (5-year OS 84%), the prognostic role of IRS grouping, grade of malignancy, tumor size and local invasiveness, the poor prognosis for patients with the MPNST histotype [12] and with metastases at diagnosis. It is worth noting that treatment for extremity NRSTS proved more effective over the years, while this was not the case for RMS.…”
Section: Discussionsupporting
confidence: 91%
“…In vivo, doxorubicin also showed no effect on established tumors and no added benefit to RAD001 alone. This result is consistent with the generally poor response to chemotherapy shown by MPNST patients (1). In combination with RAD001, doxorubicin did not show significant added benefit when cell viability was assayed.…”
Section: Discussionsupporting
confidence: 79%
“…MPNSTs are treated by resection of the tumor followed by treatment with chemotherapeutic agents, including anthracyclines and alkylating agents. A retrospective study of patients treated with various chemotherapeutics found that the use of chemotherapy increased overall and event-free survival in MPNSTs (1). However, the 5-year survival for patients with unresectable tumors and metastatic MPNST was 30% and patients with NF1 had lower response rate than those with sporadic cases (17.6% versus 55%).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effectiveness of adjuvant chemotherapy for MPNST remains controversial [7]. However, it is worth noting that relatively high overall response rates (45%) have been found in paediatric patients with MPSNTs who received adjuvant chemotherapy [14]. Nevertheless, the efficacy of adjuvant chemotherapy in the treatment of MPNSTs warrants further investigation in a large-scale, multicenter, prospective trial.…”
Section: Discussionmentioning
confidence: 99%